Pengembangan Bahan Ajar Mata Kuliah Kajian Seni Rupa Nusantara Pada Program Studi Pendidikan Seni Rupa Program Pascasarjana Universitas Negeri Makassar - Yunus, Pangeran Paita; Ahmad, Abd Aziz (Nuansa Journal of Arts and Design, 2017)
This study aims to 1) develop teaching material subjects Visual Arts archipelago study to assess the ability to understand, appreciate, and analyze student of aspects of the historical background, concepts, and works of art in the archipelago that includes all the works of art that exist throughout Indonesia, 2) assess the feasibility of teaching material Study subjects archipelago Arts Education Master of Fine Arts Graduate Program, State University of Makassar valid, practical, and effective. This study refers to the development of procedures developed by Borg & Gall consisting of ten steps systematically arranged, with the explanation that is easy to understand, and be able to direct the developer from the beginning to the end of the study. In the research development of teaching materials is only up to nine steps, activities of dissemination or distribution of products is not done because of limited funds and time researchers.Components of the learning package that was developed in this research is the textbook, media presentations, and tests appreciation. Stages in the research and development of instructional package consists of two phases: a preliminary study phase and the development phase, while the implementation phase of testing and evaluation phase will be conducted in the second year of the study. In this study, the instrument was developed questionnaires, observation sheets, and tests appreciation. Questionnaire consisted of a questionnaire developed for the validator (matter experts and media specialists), a questionnaire for faculty, and questionnaires for students. Questionnaire for the validator is used to validate the learning package, and obtaining feedback or suggestions to revise the package developed. Questionnaire for lecturers used to determine the response of lecturers to learning package that was developed, and advice necessary to revise the package. Similarly, the questionnaire for the students is used to determine the response and suggestions of students towards learning package is developed